Teknik Tazkiyatun An-Nafs dalam Meningkatkan Kesadaran Diri Santri - Hamid, Hamid; Mohamat Hadori , Mohamat Hadori (Konseling At-Tawazun, 2022)
Tazkiyatun an-nafs is a method used by people who have the ability to educate their souls so that they are always clean and protected from all forms of ugliness and sin. People who have an attitude of tazkiyatun an-nafs will tend to bring themselves to positive things because their soul, mind, and attitude are clean from sin and other bad things. The purpose of this study was to describe the tazkiyatun an-nafs technique in increasing self-awareness of students at the Salafiyah Syafi’iyah Islamic Boarding School Sukorejo. The research met- hod used is a qualitative research method, namely a research procedure that produces des- criptive data in the form of speech or writing and observable behavior from the person (sub- ject) itself. The conclusions from the research on the tazkiyatun an-nafs technique are: pu- rifying the soul, giving something worthy of the soul, having noble character, strengthening faith, building brotherly relations on the foundation of piety, making friends with pious pe- ople and staying away from bad people, improving the environment. , move and be alone if in a crowded place can not make the heart calm.